The Role of Environmental Product Declarations in the Decarbonization of Building Materials and Components - Francesco Asdrubali; Gianluca Grazieschi; Dante Maria Gandola (Energies)
As energy efficiency measures have reduced the operational carbon footprint of buildings, the significance of embodied carbon has increased. Efforts by all construction players, including material and component manufacturers, are needed to avoid burdens shifting towards embodied impacts. Environmental Product Declarations (EPDs) can represent useful instruments to push the decarbonization of construction materials. This study examines EPDs to assess the embodied GWP of insulation materials, bricks, concrete, cement, steel, and natural stones. The variance structure of the GWP was studied for each material, the main variation parameters were detected, and statistically significant categories were identified. For each category reference values were calculated (i.e., mean or median values, lower and upper interquartile ranges, and box plot whiskers) which can be useful for manufacturers to reduce the impact of their products, for EPD verifiers to detect outliers, and for designers to determine safety coefficients for using EPD data in the early design stage. Consolidated results were achieved for materials produced through standardized processes whose GWP variability was mainly structured around universal physical properties or production techniques. More localized or artisanal products demonstrate higher decarbonization potential but require further segmentation and additional GWP data to establish more robust reduction benchmarks.